International experience in the strategy and policy of developing a regional innovation system - Anh, Cao Thi Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
The regional innovation system approach has been developed for the past few decades, there are many studies on the regional innovation system because this approach allows to explore the aspect of innovation capabilities of through detailed analysis of the main actors in the system, explaining the differences in innovative activities and competitive capacity of different regions. On the other hand, this approach is also developed by the fact that the regional innovation system is expected to be found everywhere and studies have shown that it is possible, all regions exist. The regional innovation system is not only the areas with strong prerequisites for innovating. So what is the regional innovation system? What role do actors in the regional innovation system play and how do they interact with each other? What are the policies to develop the regional innovation system? What experience do countries have in developing regional innovation systems? Those are the issues this article wishes to be addressed. Code: 19121001